2016
DOI: 10.1088/2053-1583/3/3/035006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of above 20 K superconductivity of blue phosphorus bilayer with metal intercalations

Abstract: Abstract. First-principles calculations predicted monolayer blue phosphorus to be an alternative two-dimensional allotrope of phosphorus, like the recently discovered monolayer black phosphorus. Due to its unique crystalline and electronic structure, blue phosphorus may be a promising candidate as a BCS-superconductor after proper intercalation. In this study, using first-principles calculations, the favorable intercalation sites for some alkali metals and alkaline earths have been identified for Blue-P bilaye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
1
38
2
Order By: Relevance
“…In general, the intravalley couplings can have different coupling potentials and therefore differing amplitudes in each valley. The observation of intrinsic superconductivity in BP has attracted much attention [49][50][51][52][53][54] as well as controversies 55,56 . Here we assume that the superconductivity can be induced extrinsically in the BP by making use of the proximity effect.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the intravalley couplings can have different coupling potentials and therefore differing amplitudes in each valley. The observation of intrinsic superconductivity in BP has attracted much attention [49][50][51][52][53][54] as well as controversies 55,56 . Here we assume that the superconductivity can be induced extrinsically in the BP by making use of the proximity effect.…”
Section: Resultsmentioning
confidence: 99%
“…In order to accurately calculate interlayer binding in blue phosphorus, we need an accurate representation of the monolayer to serve as a reference. For computational convenience, we fixed the P-P bond length to 2.23Å which is the average of two different bond lengths of black phosphorus [28] and is also within the range of the bond lengths reported in previous DFT studies on blue phosphorene [29][30][31]. Small variations of the P-P bond length were found to have little effect on our DMC results presented below.…”
Section: A Optimizing the Monolayermentioning
confidence: 96%
“…Also, it has been found that black phosphorus in both orthorhombic and rhombohedral structures can intrinsically develop superconductivity [21][22][23][24][25][26][27][28][29][30][31] . However, the dominant pairing type in BP has brought up discussions and is still unclear.…”
Section: Introductionmentioning
confidence: 99%